Obtained intergeneric hybrids from distant hybridization between Lagerstroemia and Heimia - Qifang Lin; Xin Wang; Zhiting Wan; Jingting Tao; Xiufeng Chi; Ping Shen; Ming Cai; Jia Wang; Tangren Cheng; Qixiang Zhang; Huitang Pan (Ornamental Plant Research)
Lagerstroemia comes in a variety of bright petal colors, but it lacks yellow flowers. To breed yellow-flowered cultivars, eight Lagerstroemia and two Heimia species were used for intergeneric hybridization. Mentor pollen was applied to enhance pollination efficiency, and GA3 and 2,4-D were sprayed onto stigmas after pollination to extend hybrid fruit development. Progenies were obtained by embryo rescue and identified as hybrids between Lagerstroemia and Heimia by SSR markers. The results showed that there was strong reproductive isolation between Lagerstroemia and Heimia. When Lagerstroemia was the female parent, the fruits dropped within 5 d after pollination, and when Heimia was the female parent, the fruits did not drop, but dried up within 15 d. After pollination, pollen tubes of Heimia in the styles of Lagerstroemia halted at one-fourth of the style length, with few entering the ovary. While pollen tubes of Lagerstroemia in the style of Heimia reached the stigma base but rarely entered the ovary. Mentor pollen reduced callose production and promoted the growth of pollen tubes. Most hybrid embryos aborted on plants naturally, and applying 200 mg·L−1 GA3 to Lagerstroemia pistils and 20 mg·L−1 2,4-D to Heimia pistils promoted some of the hybrid fruits to the heart-shaped embryo stage. In our experiment, a total of 12,350 flowers were pollinated, and only four hybrid progenies were obtained by embryo rescue, with one hybrid confirmed as a true hybrid. The results provided a foundation for breeding yellow-flowered Lagerstroemia cultivars.